NETWORK SIZE SIMULATION-BASED STUDY OF ROUTING PROTOCOLS IN WIRELESS AD HOC NETWORK - Augustine Chidiebere Onuora; Eyo Edmund Essien; Felix U Ogban (STMIK Pringsewu Lampung, 2021)
The extensive potential of wireless ad hoc networks in many different fields has recently gained significant research attention. Multihop routing is an important aspect that determines the overall network performance to a large extent. Several routing protocols for wireless ad hoc networks have been proposed with the aim of optimizing various aspects of network routing. As networks grow in size, computer network performance analysis becomes increasingly necessary. A simulation approach is often very useful. This research studies three common routing protocols for wireless ad hoc networks to compare the performance as it relates to the network size. Protocols considered in this study are; Ad hoc On-Demand Distance Vector (AODV), Destination-Sequenced Distance Vector (DSDV), and Optimized Link-State Routing Vector (OLSR) classified as reactive routing protocol (AODV) and proactive routing protocol (OLSR and DSDV). These protocols were simulated using the Network Simulator 3 (NS3) using a performance-compared based on the size of the network. Varying network sizes of 30, 60 and 100 nodes were simulated. The result showed that AODV performed better as the network size increases.